Adaptor protein complex 4 deficiency: a paradigm of childhood-onset hereditary spastic paraplegia caused by defective protein trafficking. (9th January 2020) - Behne, Robert; Teinert, Julian; Wimmer, Miriam; D'Amore, Angelica; Davies, Alexandra K; Scarrott, Joseph M; Eberhardt, Kathrin; Brechmann, Barbara; Chen, Ivy Pin-Fang; Buttermore, Elizabeth D; Barrett, Lee; Dwyer, Sean; et al.
Abstract: Deficiency of the adaptor protein complex 4 (AP-4) leads to childhood-onset hereditary spastic paraplegia (AP-4-HSP): SPG47 ( AP4B1 ), SPG50 ( AP4M1 ), SPG51 ( AP4E1 ) and SPG52 ( AP4S1 ). This study aims to evaluate the impact of loss-of-function variants in AP-4 subunits on intracellular protein trafficking using patient-derived cells. We investigated 15 patient-derived fibroblast lines and generated six lines of induced pluripotent stem cell (iPSC)-derived neurons covering a wide range of AP-4 variants. All patient-derived fibroblasts showed reduced levels of the AP4E1 subunit, a surrogate for levels of the AP-4 complex. The autophagy protein ATG9A accumulated in the trans-Golgi network and was depleted from peripheral compartments. Western blot analysis demonstrated a 3–5-fold increase in ATG9A expression in patient lines. ATG9A was redistributed upon re-expression of AP4B1 arguing that mistrafficking of ATG9A is AP-4-dependent. Examining the downstream effects of ATG9A mislocalization, we found that autophagic flux was intact in patient-derived fibroblasts both under nutrient-rich conditions and when autophagy is stimulated. Mitochondrial metabolism and intracellular iron content remained unchanged. In iPSC-derived cortical neurons from patients with AP4B1 -associated SPG47, AP-4 subunit levels were reduced while ATG9A accumulated in the trans-Golgi network. Levels of the autophagy marker LC3-II were reduced, suggesting a neuron-specific alteration in autophagosome turnover. Neurite outgrowth and branching were reduced in AP-4-HSP neurons pointing to a role of AP-4-mediated protein trafficking in neuronal development. Collectively, our results establish ATG9A mislocalization as a key marker of AP-4 deficiency in patient-derived cells, including the first human neuron model of AP-4-HSP, which will aid diagnostic and therapeutic studies.